Commentary on Kopiez, Wolf, and Platz: The impact of playing from memory on performance evaluation - Gingras, Bruno (Empirical Musicology Review, 2017)
Kopiez et al. (this volume) empirically investigated the effect of playing from memory (more specifically, playing with a conspicuously visible music stand) on the evaluation of audiovisual recordings of solo instrumental performances. Their study, a replication of Williamon (1999), corroborates the finding that the presence of a music stand has a small but significant negative effect on performance evaluations. In this commentary, I present some possible explanations for this effect and discuss relevant implications for future research and for professional performers. I also provide some suggestions for improving the experimental design, such as using a better measure of musical sophistication, controlling for the potential visual distractor effect of the music stand, and developing a more comprehensive and statistically robust scale for evaluating performances.